Candolleomyces asiaticus sp. nov. (Psathyrellaceae, Agaricales), a novel species from Punjab, Pakistan - Asif, Muhammad; Izhar, Aiman; Niazi, Abdul Rehman; Khalid, Abdul Nasir (European Journal of Taxonomy, 2022)
During mycological surveys of different areas of Punjab, Pakistan, we collected a new species from the genus Candolleomyces. This is the first report of any species of this genus from Pakistan. Candolleomyces asiaticus M.Asif, A.Izhar, Niazi & Khalid sp. nov. is characterized by ellipsoid to oblong-ellipsoid (8.2 × 5 µm) basidiospores with indistinct germ pores, lageniform to utriform cheilocystidia without adhering deposits at the apices, absence of pleuro-, pileo- and caulocystidia, pileipellis with spherical, subglobose to columnar cells, and presence of clamp connections. The morpho-anatomical and molecular phylogenetic analysis of nrITS revealed its distinct phylogenetic position, further supporting the recognition of a new species.